The use of contractors on deployed operations (CONDO) in the age of austerity - Moore, David M.; Antill, Peter D. (Cranfield University, 2013)
Dr David M Moore and Peter D Antill from Cranfield University highlight the issues surrounding the increased use of contractors on the front line